2017
DOI: 10.1007/s11367-016-1241-3
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment in road infrastructure planning using spatial geological data

Abstract: Purpose The purpose of the study was to outline and demonstrate a new geographic information system (GIS)-based approach for utilising spatial geological data in three dimensions (i.e. length, width and depth) to improve estimates on earthworks during early stages of road infrastructure planning. Methods This was undertaken by using three main methodological steps: mass balance calculation, life cycle inventory analysis and spatial mapping of greenhouse gas (GHG) emissions and energy use. The mass balance calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
(17 reference statements)
0
10
1
Order By: Relevance
“…Even though the importance of construction machinery has been highlighted in the LCA community (Barandica et al 2013;Garbarino et al 2014;Barati and Shen 2016;Karlsson et al 2017), very few studies were found that focus on the issue of the environmental impacts of construction machinery. Instead, the LCA of machinery has been integrated into bigger systems, like construction projects, in an effort to provide an overarching perspective on the potential impacts in the studied systems (Park et al 2003;Cass and Mukherjee 2011;Barandica et al 2013;Melanta et al 2013;O'Born et al 2014).…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…Even though the importance of construction machinery has been highlighted in the LCA community (Barandica et al 2013;Garbarino et al 2014;Barati and Shen 2016;Karlsson et al 2017), very few studies were found that focus on the issue of the environmental impacts of construction machinery. Instead, the LCA of machinery has been integrated into bigger systems, like construction projects, in an effort to provide an overarching perspective on the potential impacts in the studied systems (Park et al 2003;Cass and Mukherjee 2011;Barandica et al 2013;Melanta et al 2013;O'Born et al 2014).…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…Naturally, the variation in such default data is large (because, by necessity is has been collected from different other sources). For example, the assumed default diesel use for soil excavation is several times higher in Klimatkalkyl 3.0 than in the LICCER model and the assumed default quantity of explosives for rock blasting is twice as high (Karlsson et al, 2017). In terms of traffic, default data (for example fuel consumption) may vary between different roads depending on local conditions such as road incline and speed limit.…”
Section: Availability Of Project Specific and Default Input Datamentioning
confidence: 99%
“…The greatest opportunity to influence life cycle impacts of transport occurs in early planning stages (Hammervold, 2014;Karlsson et al, 2017;O'Born et al, 2016), such as choice of road corridor and construction type. The choice of road corridor influences route length and construction type and has thereby a large influence on environmental impacts from future traffic on the road and on impacts from road construction, operation, and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…A conclusion of this is that if the purpose is to make road transports more energy efficient it can be better to accept higher energy use for the infrastructure if it leads to lower fuel use of vehicles since it can result in lower total energy use (Carlson, 2011). A proposed GIS-based approach shows promising results for usage in LCA at an early stage of road infrastructure planning (Karlsson et al, 2017).…”
Section: Roads and Pavementsmentioning
confidence: 99%